1999
DOI: 10.1128/jb.181.5.1610-1616.1999
|View full text |Cite
|
Sign up to set email alerts
|

The P alkBFGHJKL Promoter Is under Carbon Catabolite Repression Control in Pseudomonas oleovorans but Not in Escherichia coli alk + Recombinants

Abstract: The alk genes are located on the OCT plasmid ofPseudomonas oleovorans and encode an inducible pathway for the utilization of n-alkanes as carbon and energy sources. We have investigated the influence of alternative carbon sources on the induction of this pathway in P. oleovorans andEscherichia coli alk + recombinants. In doing so, we confirmed earlier reports that induction of alkane hydroxylase activity in pseudomonads is subject to carbon catabolite repression. Specifically, synthesis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…However, not all organic acids can induce a CCR effect and, even more intriguingly, some of them have a clear effect in some cases, but not in others. For example, citrate allows a good expression of the P. putida GPo1 OCT plasmid alkane degradation pathway (Yuste et al, 1998;Staijen et al, 1999), but has a repressive effect on the P. putida H phenol degradation genes (MĂŒller et al, 1996) and on the P. putida CA-3 pathway for styrene assimilation (O'Leary et al, 2001). This may be due to specific differences in the bacterial strains or in the genes analysed or the experimental conditions used.…”
Section: Ccr In Pseudomonas : Preferred Substratesmentioning
confidence: 99%
“…However, not all organic acids can induce a CCR effect and, even more intriguingly, some of them have a clear effect in some cases, but not in others. For example, citrate allows a good expression of the P. putida GPo1 OCT plasmid alkane degradation pathway (Yuste et al, 1998;Staijen et al, 1999), but has a repressive effect on the P. putida H phenol degradation genes (MĂŒller et al, 1996) and on the P. putida CA-3 pathway for styrene assimilation (O'Leary et al, 2001). This may be due to specific differences in the bacterial strains or in the genes analysed or the experimental conditions used.…”
Section: Ccr In Pseudomonas : Preferred Substratesmentioning
confidence: 99%
“…comm.). The AlkS/PalkB expression system is not subject to catabolite repression in E. coli (Staijen et al, 1999). AlkS/PalkB has been used for tightly controlled and high-level expression of recombinant xylene oxidase for biotransformation of styrene into (S)-styrene oxide (Panke et al, 1999), and it has also been shown to function well for induced production of recombinant proteins under HCDC of E. coli (Makart et al, 2007).…”
Section: The Alks/palkb Regulator/promoter Systemmentioning
confidence: 99%
“…Biocatalysts based on bacterial wild-type strains, which are able to assimilate hydrocarbons as sole source of carbon and energy, are often tolerant to toxic effects of such growth substrates and their oxidized metabolites (Ramos et al, 2002) and often show high oxidation activities ). Yet, diverse enzymes and regulatory systems involved in the assimilation of hydrocarbons (Jimenez et al, 2002;Nelson et al, 2002) may cause degradation of the products of interest, byproduct formation, and catabolite repression (Santos et al, 2000;Staijen et al, 1999). As a result, metabolic pathway engineering and biochemical process engineering are often crucial for the development of a viable process based on hydrocarbon degraders.…”
Section: Introductionmentioning
confidence: 99%